Forest succession after a major anthropogenic disturbance: a case study of the Jewish Forest in the Bohemian Forest, Czech Republic - J. Bednařík; V. Čada; K. Matějka (Journal of Forest Science, 2014)
The knowledge of forest development after disturbances, particularly anthropogenic disturbances, is of major importance for forest management. Many areas of mountain forests in Europe have been affected by human activities such as felling and livestock grazing in the past and then left for natural succession. Those forests provide several ecosystem services (e.g. soil or avalanche protection) and therefore it is vital to know their developmental processes. The Norway spruce forest stand in the area of Medvědí Mt. (Šumava National Park, Czech Republic), known as the Jewish Forest, is considered an example of succession after anthropogenic disturbances. This study aimed to: (1) analyse the history of disturbances which affected the locality, (2) describe the subsequent process of forest succession which led to the development of the present forest formation. We conducted a dendrochronological analysis and a spatial analysis. The main cohort was established after a period of disturbances in the first half of the 20th century. Both natural (windstorm) and anthropogenic (logging and livestock grazing) disturbances coincided during this period. Regeneration of low density was restricted to a short period after the disturbance and was likely dependent on the occurrence of proper microsites. Later, regeneration was probably obstructed by lack of convenient microsites and high competition of the herb layer. Nowadays, new regeneration emerges together with proper microsite at decaying wood and near mature trees. We conclude that anthropogenic disturbances can limit the density and heterogeneity of regeneration, which leads to the establishment of sparse stand. This structure can persist for decades before proper microsites accumulate and enable regeneration.